Knowledge, Attitude and Practice of Research Ethics among Researchers in Nepal - Namita Ghimire; Santoshi Adhikari; Subhanshi Sharma; Rojina Basnet; Richa Acharya; Shashi Verma; Pradip Gyanwali (Journal of Nepal Medical Association, 2024)
Introduction: The universal health research ethical principles must be adhered to ensure a balance between science and safeguarding participants' rights, safety and dignity. A cross-sectional study was conducted to assess the knowledge, attitude, and practice of research ethics among researchers in Nepal.